Sorsby fundus dystrophy – A review of pathology and disease mechanisms. (December 2017) - Christensen, David R.G.; Brown, Ffion E.; Cree, Angela J.; Ratnayaka, J. Arjuna; Lotery, Andrew J.
Abstract: Sorsby fundus dystrophy (SFD) is an autosomal dominant macular dystrophy with an estimated prevalence of 1 in 220, 000 and an onset of disease around the 4th to 6th decade of life. Similar to age-related macular degeneration (AMD), ophthalmoscopy reveals accumulation of protein/lipid deposits under the retinal pigment epithelium (RPE), referred to as drusen, in the eyes of patients with SFD. SFD is caused by variants in the gene for tissue inhibitor of metalloproteinases-3 ( TIMP3 ), which has been found in drusen-like deposits of SFD patients. TIMP3 is constitutively expressed by RPE cells and, in healthy eyes, resides in Bruch's membrane. Most SFD-associated TIMP3 variants involve the gain or loss of a cysteine residue. This suggests the protein aberrantly forms intermolecular disulphide bonds, resulting in the formation of TIMP3 dimers. It has been demonstrated that SFD-associated TIMP3 variants are more resistant to turnover, which is thought to be a result of dimerisation and thought to explain the accumulation of TIMP3 in drusen-like deposits at the level of Bruch's membrane. An important function of TIMP3 within the outer retina is to regulate the thickness of Bruch's membrane. TIMP3 performs this function by inhibiting the activity of matrix metalloproteinases (MMPs), which have the function of catalysing breakdown of the extracellular matrix. TIMP3 has an additional function to inhibit vascular endothelial growth factor (VEGF) signalling and thereby to inhibit angiogenesis. However, it is unclear whether SFD-associated TIMP3 variant proteins retain these functions. In this review, we discuss the current understanding of the potential mechanisms underlying development of SFD and summarise all known SFD-associated TIMP3 variants. Cell culture models provide an invaluable way to study disease and identify potential treatments. These allow a greater understanding of RPE physiology and pathophysiology, including the ability to study the blood-retinal barrier as well as other RPE functions such as phagocytosis of photoreceptor outer segments. This review describes some examples of such recent in vitro studies and how they might provide new insights into degenerative diseases like SFD. Thus far, most studies on SFD have been performed using ARPE-19 cells or other, less suitable, cell-types. Now, induced pluripotent stem cell (iPSC) technologies allow the possibility to non-invasively collect somatic cells, such as dermal fibroblast cells and reprogram those to produce iPSCs. Subsequent differentiation of iPSCs can generate patient-derived RPE cells that carry the same disease-associated variant as RPE cells in the eyes of the patient. Use of these patient-derived RPE cells in novel cell culture systems should increase our understanding of how SFD and similar macular dystrophies develop. Highlights: Sorsby fundus dystrophy (SFD) is a dominant macular disease leading to blindness. We estimate the prevalence of SFD at approximately 1 in 220, 000. SFD is driven by multiple different variations in TIMP-3, which are summarised. Mechanisms by which variants in TIMP3 might lead to disease are discussed. We propose that patient-derived stem cells may provide a new model to study SFD.